2003
DOI: 10.1124/mol.63.2.439
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Induced by (E)-5-(2-Bromovinyl)-2′-deoxyuridine in Varicella Zoster Virus Thymidine Kinase-Expressing Cells Is Driven by Activation of c-Jun/Activator Protein-1 and Fas Ligand/Caspase-8

Abstract: The molecular mode of cell killing by the antiviral drug (E)-5-(2-bromovinyl-2Ј-deoxyuridine (BVDU) was studied in Chinese hamster ovary (CHO) cells stably transfected with the thymidine kinase gene (tk) of varicella zoster virus (CHO-VZVtk). The colony-forming ability of the cells was reduced to Ͻ1% at a concentration of ϳ1 M BVDU, whereas for nontransfected cells or cells transfected with tk gene of herpes simplex virus type 1 (CHO-HSVtk), a 1000-fold higher dose was required to achieve the same response. BV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…For monitoring drug-induced apoptosis and necrosis within the same cell population, annexin V-FITC/PI double staining combined with flow cytometry was applied. The protocol was conducted as described (32). The metabolic activity was determined by 3-(4,5-dimethyldiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay as already described (33).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For monitoring drug-induced apoptosis and necrosis within the same cell population, annexin V-FITC/PI double staining combined with flow cytometry was applied. The protocol was conducted as described (32). The metabolic activity was determined by 3-(4,5-dimethyldiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay as already described (33).…”
Section: Methodsmentioning
confidence: 99%
“…To follow progression of cells through the cell cycle, cells were pulse-labeled with 10 μM BrdU for 30 min and thereafter the thymidine analog was washed out and cells were non-treated or treated with BPDE. After treatment, cells were fixed, incubated with mouse anti-BrdU antibody (BD Biosciences) and subsequently with Alexa Fluor 488-coupled anti-mouse antibody (Millipore), and stained with PI as described (32). Cells were analyzed by flow cytometry (FACS Calibur, BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Progression of cells through the cell cycle was analyzed by flow cytometry as previously described (18). In brief, cells were continuously treated with topotecan, and after different time points, fixed with ethanol, incubated with 0.1 mg/mL RNase in PBS for 1 hour, and stained with propidium iodide (25 Ag/mL) prior to flow cytometry (CellQuestPro, BD, Heidelberg, Germany).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of JNK is an obligatory event for release of Smac during stress-induced cell death [72]. However, it was suggested that JNK activation is followed by induction of Fas L/Fas signaling, the receptor dependent death pathway which might either activate and translocate mitochondria protein Bid or might be mitochondria independent [73][74][75][76][77][78][79][80][81]. In our previous study, we showed that (Ac) 5 GP mediates tumor cell death via induction of PKCδ/JNK/Fas L cascades, which subsequently activate caspase 8 and caspase 3, thus promoting the apoptotic signal [82] (Fig.…”
Section: (Ac) 5 Gp and Apoptosismentioning
confidence: 99%